2018
DOI: 10.15562/jdmfs.v3i3.794
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness disinfection of 2% glutaraldehyde and 4.8% chloroxylenol on tooth extraction instruments in the Department of Oral Maxillofacial and Surgery, Faculty of Dentistry, University of North Sumatera

Abstract: Material and Methods: This was an experimental study with posttest only control group design approach. Purposive technique is applied to collect samples which are lower molar extraction forceps. In this study, sample were divided into 2 groups and each consisting of 18 instruments. The treatment group was treated with 2% glutaraldehyde while the control group was treated with 4.8% chloroxylenol. Each instrument was pre-cleaned using a brush, water and soap for both groups underwent the disinfection process. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The research by Riza et al in 2018 showed 11 out of 18 mandibular molar tooth extraction forceps which were cleaned using 4.8% chloroxylenol did not form bacterial colonies, and seven mandibular molar tooth extraction forceps had a maximum bacterial count of 812 Á 10 3 CFU/mL and the average number of bacterial colonies formed was 82.5. 13 This is in accordance with the results of this study: in all research samples bacterial colonies still formed although with fewer bacterial colonies on average. Guther et al, 2020, who conducted research on the skin and the hospital environment, found that 4.8% chloroxylenol could interfere with the metabolic activity of Grampositive bacteria by 38.9% and Gram-negative by 60.7%.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The research by Riza et al in 2018 showed 11 out of 18 mandibular molar tooth extraction forceps which were cleaned using 4.8% chloroxylenol did not form bacterial colonies, and seven mandibular molar tooth extraction forceps had a maximum bacterial count of 812 Á 10 3 CFU/mL and the average number of bacterial colonies formed was 82.5. 13 This is in accordance with the results of this study: in all research samples bacterial colonies still formed although with fewer bacterial colonies on average. Guther et al, 2020, who conducted research on the skin and the hospital environment, found that 4.8% chloroxylenol could interfere with the metabolic activity of Grampositive bacteria by 38.9% and Gram-negative by 60.7%.…”
Section: Discussionsupporting
confidence: 92%
“…9 In the 4.8% chloroxylenol treatment group, mandibular molar extraction pliers were soaked for 60 minutes and then samples were taken. 13 In the negative control group (Aquadest) the pliers were rinsed with distilled water, then a sample was taken.…”
Section: Ozone Water Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen peroxide is also widely used in the household and in medical field as antiseptic, bleaching or oxidator material and disinfectant as well as surface / environmental cleaning. 6, 9 The spaulding classification describes three instruments/risk categories (critical, semi-critical and non-critical), each of which has specific reprocessing requirements. According to the Spaulding classification, lower molar extraction forceps are classified as critical items, objects that enter sterile tissue or vascular system should be sterile because any microbial contamination could result in disease transmission.…”
Section: Discussionmentioning
confidence: 99%